Development of Swimming Learning Media Based on Interactive Multimedia Applications Through Computers and Smartphones - Susena, Satrio Jaya; Sugiharto, Sugiharto; Kusuma, Donny Wira Yudha (Journal of Physical Education and Sports, 2021)
Swimming is a water sport that involves movement abilities in the water; yet, the lack of swimming learning media that encourages movement impedes the swimming learning process. This study developed learning media based on interactive multimedia applications that can be accessed via computers and smartphones in conjunction with swimming lessons, as well as to determine and analyze the effectiveness of using interactive multimedia applications under swimming lessons. Development research or educational research and development was the research design. The research subjects and locations are health and sport education students and teachers at private universities in the Kuningan and Cirebon areas. The research resulted in the development of swimming learning media products based on interactive multimedia applications named PRM Mobile Swimming Learning. These products can be accessed via computers and smartphones and are used to assist in the process of swimming learning. Student assessments of the display quality and supporting features (attractiveness and convenience) show that the development of swimming learning media based on interactive multimedia apps is of “Very Good” quality, scoring 87%. While student assessments of material quality and content in swimming learning (utility) indicated that the development of swimming learning media based on interactive multimedia apps was “Very Good” in quality 84%.